Adipose tissue: Another target organ for lead accumulation? A study on sardinian children (Italy). (10th September 2013) - Vallascas, Elisabetta; De, Alessandro; Deiana, Fabrizio; Banni, Sebastiano; Sanna, Emanuele
<x xml:space="preserve">Abstract</x> Objectives This study analyzes the relationship between lead levels and adipose tissue in Sardinian children. As an environmental pollutant, lead occurs in two different chemical forms: inorganic and organic lead; organic lead is present in the environment mainly as lead‐alkyls (tetramethyl and tetraethyl lead). The lead‐alkyls are characterized by their liposolubility; because of this characteristic, the behavior of organic Pb in the organism is similar to that of persistent organic pollutants (POPs). In fact, the high liposolubility of POPs, synthetic chemical substances highly resistant to biodegradation in both the environment and the human body, gives them a preferential tendency to accumulate in adipose tissue. Methods The study sample consisted of 759 children between 11 and 15 years resident in various municipalities of Sardinia. Hair lead levels (PbH) were used as the biomarker of exposure, while several anthropometric indexes were adopted to evaluate the adipose tissue: weight, body mass index, waist circumference, waist to hip circumference ratio, and sum of skinfolds (Σskf). Results The results of the multivariate ridge regression analysis, controlling for sex and age, show a significant positive relationship between logPbH and logΣskf but not the other adiposity indicators. Conclusions This results suggests that organic lead tends to accumulate in adipose tissue, although it would be appropriate to measure lead levels in the adipose tissue itself in order to verify the results. Hence this tissue could be considered a possible new biological matrix for the evaluation of environmental lead exposure. Am. J. Hum. Biol. 25:789–794, 2013. © 2013 Wiley Periodicals, Inc.